Mushkilah Kitābat al-Baḥth wa Ḥalluhā fī Qism Ta'līm al-Lughah al-'Arabiyah Jāmi'at Sunan Kalijaga al-Islāmiyah al-Ḥukūmiyah - Agung Setiyawan (ALSINATUNA, 2017)
Department of Arabic Education UIN Sunan Kalijaga has not set a policy on the obligation to write thesis in Arabic. Therefore, there are students who prefer to write their thesis in Indonesian. The article aims to find out the factors that cause students to prefer to write their thesis in Indonesian, the absence of policy writing thesis with Arabic and formulate a set of policy to upgrade the quality of graduate students by improving their paper. This is qualitative descriptive research in field research method. The data collection method gathered from questionare and interview. The data source were collected from the students who are still completing and had finished their undergraduste paper, and also the leader of Arabic Education Department as the stakeholder.The result shows eight factors that cause the students prefer to compose their undergraduate papers in Indonesian language. The are also four reasons to consider that it is not compulsory for the students to write the undergraduate paper in Arabic language. More over, there are three sets of policy about composing undergraduate paper to improve the quality of the graduate students the last is the steps of the realization of each activities.